Maximum blood lactate concentration after two different specific tests in freestyle swimming - Rozi, G.; Thanopoulos, V.; Dopsaj, M. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Lactic acid constitutes a useful tool for the determination of anaerobic capacity for researchers and trainers. The highest lactate levels have been recorded following the swimming distances of 100 and 200 meters (Avlonitou 1996). The rate of lactic acid production in muscle fibres depends on swimming speed, rate of oxygen consumption and type of muscle fiber (Maglischo 2003). There is no much information for the comparison of different maximum events in order to determine the most adequate training method for maximal accumulation and tolerance of lactic acid. METHODS: In this study participated 8 swimmers (4 males and 4 female). The following variables were examined: Age (in years), Body Stature (BS in cm) , Body Mass (BM in kg), At the beginning, they swam 2x100 meters freestyle with maximum intensity and 10 sec stop. Afterwards, in two days time the same athletes were tested in 4x50m and 10 sec stop. Time performance and blood lactate accumulation were measured in both tests. In order to determine maximum concentration of lactic acid, samples of blood were taken in 3rd, 5th and 7th minute of recovery time and analysed using the the Lactate Scout. RESULTS: The average time performance of swimmers in 2x100 meters freestyle was 120,79±5,67sec and 146,32±5,26sec while in 4x50m was 120,43±5,96sec and 139,64±5,44sec in male and female respectively. Maximum accumulation of lactic acid in 2x100 meters freestyle was 11,3±2,6 and 10,3±2,1 mmol/l, in relation to the test of 4x50 that was 12,1±2,3 and 12,5±3,9 mmol/l in male and female respectively. Significant correlation was found between the two tests only in female (r=0.871; p<0.05). DISCUSSION: The main finding of the present study was that the blood lactate values measured in 3rd, 5th and 7th min post-exercise demonstrated significantly greater correlation between the two tests in female in 4x50m. From this occurs a definition of a test for the swimmers at 4x50m free-style, which will be further used to improve the technology of swimmers` sport training (Avlonitou 1996). The results obtained showed that the tested female swimmers swam at 4x50m more efficiently than their male counterparts.